Genetic diversity of Vif protein in human immunodeficiency virus type 1 variants (Retroviridae: Orthoretrovirinae: Lentivirus: Human immunodeficiency virus-1) that circulated in the Moscow region in 2019–2020 - Anastasiia A. Antonova; Larisa A. Protasova; Kristina V. Kim; Iana M. Munchak; Ekaterina N. Mezhenskaya; Elena A. Orlova-Morozova; Alexander Yu. Pronin; Alexey G. Prilipov; Anna I. Kuznetsova (Вопросы вирусологии)
Introduction. The Vif protein counteracts cellular deaminases, APOBEC3, which prevent viral replication. Vif is used for development of therapeutic agents. Natural polymorphisms in Vif can affect its functionality and may be associated with accelerated progression of HIV-infection to the AIDS. The study of Vif features in HIV-1 variants circulating in Russia has not been conducted previously.